-2x(4x² - 5x + 3) Distribute/multiply -2x into (4x² - 5x + 3)
(4x²)(-2x) - (5x)(-2x) + (3)(-2x)
-8x³ + 10x² - 6x
Your answer is the 3rd option
First you have to find the angle B (check attachment)
![B = 180^{\circ} - 137^{\circ} = 43^{\circ}\\](https://tex.z-dn.net/?f=B%20%3D%20180%5E%7B%5Ccirc%7D%20-%20137%5E%7B%5Ccirc%7D%20%3D%2043%5E%7B%5Ccirc%7D%5C%5C)
Then you can find the last angle inside the triangle, which I'll call C
![C = 180^{\circ} - 102^{\circ} - 43^{\circ} = 35^{\circ}](https://tex.z-dn.net/?f=C%20%3D%20180%5E%7B%5Ccirc%7D%20-%20102%5E%7B%5Ccirc%7D%20-%2043%5E%7B%5Ccirc%7D%20%3D%2035%5E%7B%5Ccirc%7D)
Now you can find angle A
![A = 180^{\circ} - C = 180^{\circ} - 35^{\circ} = 145^{\circ}](https://tex.z-dn.net/?f=A%20%3D%20180%5E%7B%5Ccirc%7D%20-%20C%20%3D%20180%5E%7B%5Ccirc%7D%20-%2035%5E%7B%5Ccirc%7D%20%3D%20145%5E%7B%5Ccirc%7D)
Answer:
Hi,
Step-by-step explanation:
Answer B : 51
1+4+7+10+13+16=51
The value is already in its simplest form, it cannot be reduced any further.